2019
DOI: 10.1371/journal.pone.0226074
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of polycystic ovary syndrome among obstetrician-gynecologists and endocrinologists in Northern Europe

Abstract: ObjectiveTo date, little is known about differences in the knowledge, diagnosis making and treatment strategies of health care providers regarding polycystic ovary syndrome (PCOS) across different disciplines in countries with similar health care systems. To inform guideline translation, we aimed to study physician reported awareness, diagnosis and management of PCOS and to explore differences between medical disciplines in the Nordic countries and Estonia.MethodsThis cross-sectional survey was conducted among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 24 publications
0
44
2
Order By: Relevance
“…Fertility problems and pregnancy complications were reported by a lower percentage of physicians in our study (78.3% and 19.6%, respectively) than in the North Europe study (96% and 53%, respectively) [14] . This difference could be explained by the fact that participants in the North Europe study were mainly obstetrician-gynecologists.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Fertility problems and pregnancy complications were reported by a lower percentage of physicians in our study (78.3% and 19.6%, respectively) than in the North Europe study (96% and 53%, respectively) [14] . This difference could be explained by the fact that participants in the North Europe study were mainly obstetrician-gynecologists.…”
Section: Discussioncontrasting
confidence: 76%
“…The anxiety among women with PCOS was reported by 24% of participants in the North Europe study [14] , while it was mentioned by only one physician (2.2%) in our study. The results suggest that physicians are not fully aware of psychosocial comorbidities in women with PCOS.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Chandrasekhar and Brundha in 2016 surveyed that more than 80% of the population have a knowledge about some of the symptoms of PCOS 17 . Another study showed that female with PCOS recognised the symptoms and comorbidity commonly, with the exception of psychosocial impairment which was not acknowledged meticulously 18 …”
Section: Discussionmentioning
confidence: 99%
“…Teede et al showed that weight loss of 5% to 10% can have significant clinical impacts on features of the disease 20 . Furthermore, a study of obstetrician‐gynaecologists and endocrinologists awareness of PCOS demonstrated that diagnosis and management of PCOS was suboptimal among physicians, especially psychosocial comorbidities 18 . Chemerinski et al who study the knowledge of PCOS among residents physicians revealed significant gaps in knowledge about PCOS 23 …”
Section: Discussionmentioning
confidence: 99%